2020
DOI: 10.3390/ijms21176165
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Granulysin-Based, Tn-Targeted Cytolytic Immunotoxin Using Pulsed Electric Field Technology

Abstract: Granulysin is a protein present in the granules of human cytotoxic T lymphocytes (CTL) and natural killer (NK) cells, with cytolytic activity against microbes and tumors. Previous work demonstrated the therapeutic effect of the intratumoral injection of recombinant granulysin and of the systemic injection of an immunotoxin between granulysin and the anti-carcinoembryonic antigen single-chain Fv antibody fragment MFE23, which were produced in the yeast Pichia pastoris. In the present work, we developed a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(32 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Finally, plasmids were transfected by electroporation in Pichia pastoris and the transfected colonies selected, as indicated in Materials and Methods. As indicated in our previous work [21], the yield of production of recombinant GRNLY was good, around 5 mg/L in the different batches, but the yield of production of SM3GRNLY was lower, around 2 mg/L. Taking into account the difference in molecular weight, this difference in weight yield meant a difference of 10-fold in molar yield.…”
Section: Design Of Recombinant Immunotoxin and Yield Of Productionmentioning
confidence: 53%
See 2 more Smart Citations
“…Finally, plasmids were transfected by electroporation in Pichia pastoris and the transfected colonies selected, as indicated in Materials and Methods. As indicated in our previous work [21], the yield of production of recombinant GRNLY was good, around 5 mg/L in the different batches, but the yield of production of SM3GRNLY was lower, around 2 mg/L. Taking into account the difference in molecular weight, this difference in weight yield meant a difference of 10-fold in molar yield.…”
Section: Design Of Recombinant Immunotoxin and Yield Of Productionmentioning
confidence: 53%
“…The construct coding for the 9 kDa granulysin (GRNLY) gene alone was described in our previous works [19,21]. We designed constructs to encode for the two anti-Tn immunotoxins formed by granulysin bound through a flexible linker of 23 amino acids (formed by Ser and Gly residues) to the anti-Tn scFv SM3 or AR20.5, respectively.…”
Section: Design Of Recombinant Immunotoxin and Yield Of Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these ITX, the foreign toxins are replaced by cytotoxic human proteins, thus avoiding the immune-mediated reaction against the toxin [ 24 , 25 , 26 ]. Several human proteins have been used to generate these fourth-generation ITX, including the microtubule-associated protein tau, RNases, granzyme B, death-associated protein kinase [ 26 ] and, more recently, granulysin [ 27 , 28 ]. Among those approaches, granzyme B-based ITX have been the most studied and further improved, demonstrating a therapeutic effect in several preclinical models in vivo [ 24 ].…”
Section: Immunotoxin Developmentmentioning
confidence: 99%
“…In that study, an innovative procedure based on pulsed electric field technology was used to improve the yield of production of the ITX from yeast. It was demonstrated that SM3GRNLY retained its specific binding to the Tn antigen and increased the cytotoxicity against these Tn + cell lines compared with granulysin alone [ 27 ]. However, no in vivo studies with this ITX have been reported yet.…”
Section: Antibody Fragment-based Immunotoxins In Crc: Preclinical Developmentsmentioning
confidence: 99%